2018
DOI: 10.1111/mpp.12691
|View full text |Cite|
|
Sign up to set email alerts
|

Heat shock transcription factor 3 regulates plant immune response through modulation of salicylic acid accumulation and signalling in cassava

Abstract: As the terminal components of signal transduction, heat stress transcription factors (Hsfs) mediate the activation of multiple genes responsive to various stresses. However, the information and functional analysis are very limited in non-model plants, especially in cassava (Manihot esculenta), one of the most important crops in tropical areas. In this study, 32 MeHsfs were identified from the cassava genome; the evolutionary tree, gene structures and motifs were also analysed. Gene expression analysis found th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 71 publications
(109 reference statements)
1
32
0
Order By: Relevance
“…Our findings are in line with a recent study which observed high up-regulation of HSF and heat shock proteins ( HSPs ) against biotrophic fungus [ 58 , 59 ]. HSF was also reported during bacterial infection which directly regulated Enhanced Disease Susceptibility 1 ( EDS1 ) and PR4 under SA-mediated signaling [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our findings are in line with a recent study which observed high up-regulation of HSF and heat shock proteins ( HSPs ) against biotrophic fungus [ 58 , 59 ]. HSF was also reported during bacterial infection which directly regulated Enhanced Disease Susceptibility 1 ( EDS1 ) and PR4 under SA-mediated signaling [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…From the physiological point of view, it is known that SA plays a pivotal role in the regulation of plant growth, development, in defense from biotic and abiotic stress, and in plant immune responses [4,[19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…Plant Hsfs are terminal components of a signal-transduction chain mediating the expression of abiotic-stress-responsive genes [1]. The number of Hsf members is 18 in plums [15], 21 in Arabidopsis [5], 25 in rice [6], 25 in apples [8], and 32 in cassavas [25]; these plants are diplontic. The number of Hsf members increases in allopolyploids-there are 43 in triploid banana plants [13], 59 in tetraploid soybean plants [9], and 56 in sextaploid wheat plants [10].…”
Section: Discussionmentioning
confidence: 99%